Multimodal metaphors: from language as a condition to text to the notion of texture as a meaning-making semiotic resource (Revista de Estudos da Linguagem, 2020)
Abstract: In this paper, we attempt to provide some ways of thinking about text, relating it to the concept of metaphors, multimodality and texture. Our aim is to develop new insights in meaning making and communication more generally, by bringing examples of memes; a relatively new genre, often seen on social media posts. To do so, we discuss the notion of text (HALLIDAY; HASAN, 2002; BEAUGRANDE, 1997; KRESS, 2010) and then, we discuss texture as a semiotic resource for the production of texts and its metaphors (DJONOV; VAN LEEUWEN, 2011). To exemplify some concepts and categories, we explore memes, seeking to understand their constitution as well as their qualities and potential meanings of visual textures deployed in the text to make meaning material through multimodal metaphors.Keywords: text; texture; social semiotics; multimodal metaphors.Resumo: Neste artigo, pretendemos propor algumas maneiras para se pensar a noção de texto, relacionando-a aos conceitos de metáfora, multimodalidade e textura. Nosso objetivo é desenvolver novos insights a respeito da produção de sentido e da comunicação de forma geral. Como exemplo, trazemos  memes com o bordão “É verdade esse bilete”. Como esse gênero é relativamente novo e frequentemente visto em posts nas redes sociais, discutimos a noção de texto (HALLIDAY; HASAN, 2002; BEAUGRANDE, 1997; KRESS, 2010) e de textura como um recurso semiótico para a produção de textos e suas metáforas (DJONOV; VAN LEEUWEN, 2011). Para exemplificar algumas noções e categorias, exploramos os memes, buscando compreender como eles se constituem, assim como suas qualidades e seus possíveis sentidos de texturas visuais utilizadas para produção de metáforas multimodais.Palavras-chave: texto; textura; semiótica social; metáforas multimodais.